Start-up fintech valuation (financial capital) - Frastio Oktaviano Amchory; Abdurrahman (Institute of Computer Science (IOCS), 2023)
In today's modern era, technological advances have supported the financial world in creating financial technology (fintech). One example of a fintech business is Peer to Peer Lending (P2P Lending) or Online Loans. In Indonesia, this business is growing rapidly and has good prospects, so it is hoped that P2P Lending companies can take the floor on the Indonesia Stock Exchange (IDX) to be able to attract foreign and domestic investors. One of the first fintech companies in Indonesia is Danamas. Danamas is registered and has total assets of Rp. 729,927,465,119. Before taking the floor on the IDX, it is necessary to calculate the correct valuation for Danamas. This study aims to calculate the valuation of Danamas as a fintech company. This research was conducted by processing Danamas financial report data for 2018-2020. The valuation method used is a combination of the Damodaran method and The First Chicago method with the Pre-tax Profit Margin history as a reference for obtaining estimated profits for the next 5 years. The results of this study are the company's value of Rp. 739,852,225,899. This is a positive valuation result because the company's value is greater than the total value of its assets.